Geochemistry and tectonic setting of the late Precambrian Folly River Formation, Cobequid Highlands, Avalon Terrane, Nova Scotia: a continental rift within a volcanic-arc environment - Pe-Piper, Georgia; Murphy, J. (Atlantic Geology, 1989)
The late Proterozoic Folly River Formation of the Cobequid Highlands, Nova Scotia, is a volcano-sedimentary sequence within the Avalon Terrane. The succession consists of interlayered mafic volcanic rocks and thinly laminated volcanogenic turbidites and is associated with abundant mafic dykes that are inferred to have fed the volcanic eruptions. The formation occurs exclusively between the Rockland Brook and Cobequid faults. The basalts and dykes are Fe- and Ti-rich, differentiated, within-plate continental tholeiites. Their emplacement is attributed to limited continental rifting. The Folly River Formation is similar in lithology, geochemistry and stratigraphy to the Clydesdale Formation in the Antigonish Highlands and is probably pcnecontemporaneous with arc-related volcanic sequences in both the Cobequid and Antigonish highlands. Hence it is concluded that the Folly River Formation formed in a rifting environment within a volcanic arc.